(untitled) (Research, Society and Development, 2021)
The article, based on the bases of the sociology of knowledge and the constructionist movement of contemporary social psychology, examines the mechanisms of "fabrication of reality" that operate in culture, creating and disseminating categories with values of deficit, characterized here as biases that feed back into networks of capacitant meanings in society. The “crip” epistemology, also known as “crip” theory, serves as a basis for a decolonizing understanding of the side effects of the deficit language, which intermingling in fields of knowledge widens the frontiers of the progressive illness of culture. The analysis of documents interspersed with deficit categories reiterates semiotic and political-ideological mechanisms that demarcate hierarchical values still present in the third millennium. It is questioned, to what extent anti-capacitalist movements can culturally rebel against the medical-academic-industrial complex and it is concluded that the language of deficit remains dominant, present even in the most progressive documents of the two areas studied, acting as an instrument of oppression against people with disabilities and contributing to distance them from their human rights guaranteed in the Magna Carta.